2023
DOI: 10.1097/sla.0000000000006055
|View full text |Cite
|
Sign up to set email alerts
|

Routine End-ischemic Hypothermic Oxygenated Machine Perfusion in Liver Transplantation from Donors After Brain Death

Michał Grąt,
Marcin Morawski,
Andriy Zhylko
et al.

Abstract: Objective: To assess whether end-ischemic hypothermic oxygenated machine perfusion (HOPE) is superior to static cold storage (SCS) in preserving livers procured from donors after brain death (DBD). Summary Background Data: There is increasing evidence of the benefits of HOPE in liver transplantation, but predominantly in the setting of high-risk donors. Methods: In this randomized clinical trial, livers proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The first scenario is endischemic HOPE with low SCI reduction that has been shown to reduce nonanastomotic biliary strictures in DCD livers but has failed to show a benefit in DBD livers (Figure 1A). 1,5,7 We can conclude that end-ischemic HOPE with low SCI reduction may be a promising strategy to protect the bile ducts in DCD liver grafts. In contrast, end-ischemic HOPE with high SCI reduction has been shown to reduce post-LT complications and EAD in DBD livers and may be an interesting strategy for marginal DBD grafts with expected long preservation with SCS (Figure 1B).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The first scenario is endischemic HOPE with low SCI reduction that has been shown to reduce nonanastomotic biliary strictures in DCD livers but has failed to show a benefit in DBD livers (Figure 1A). 1,5,7 We can conclude that end-ischemic HOPE with low SCI reduction may be a promising strategy to protect the bile ducts in DCD liver grafts. In contrast, end-ischemic HOPE with high SCI reduction has been shown to reduce post-LT complications and EAD in DBD livers and may be an interesting strategy for marginal DBD grafts with expected long preservation with SCS (Figure 1B).…”
Section: Discussionmentioning
confidence: 87%
“…2,3,9 In the 5 RCTs using HOPE, there is a large variation in SCI reduction, and we may distinguish 2 different subgroups. In the trials by Schlegel et al, 1 Grat et al, 7 and Van Rijn et al, 5 reduction of SCI is ≤25%, whereas in the studies by Czigany et al 4 and Ravaioli et al 8 reduction in SCI is ≥25% (25% and 39%, respectively).…”
Section: Clinical Mp Strategies and Graft Ischemiamentioning
confidence: 96%
See 1 more Smart Citation
“…In low-risk DBD donors HOPE had no impact on outcomes, however authors demonstrated significantly lower EAD-rates and post-operative complications in donor livers with higher risk, i.e. , with a donor risk index of > 1.7)[ 14 ]. Two additional RCTs were recently presented with NMP and HOPE in the United States.…”
Section: Introductionmentioning
confidence: 99%
“… 11 The potent clinical effects of HOPE, especially when using high-risk livers, have been described consistently in 5 randomized controlled clinical trials (RCT). 8 10 , 12 14 These trials could demonstrate a reduction of early allograft injury, 10 , 13 , 14 cumulative morbidity, 13 , 14 liver-related complications, 8 length of stay, 13 treatment costs, 15 , 16 and a mitigating effect on nonanastomotic biliary complications in donation after circulatory death (DCD) when using HOPE-treated allografts. 9 The most recent trial published very recently by Grąt et al 14 from Warsaw could also confirm the short-term benefits of HOPE on early allograft dysfunction and morbidity in high-risk livers with donor risk index over 1.7, but not for standard criteria allografts.…”
Section: Introductionmentioning
confidence: 99%